Macroalgae Community Structure in the Waters of Temajo Island, Mempawah Regency, West Kalimantan - Susrini, Putri Dahyu; Nurdiansyah, Syarif Irwan; Sofiana, Mega Sari Juane; Kushadiwijayanto, Arie Antasari; Safitri, Ikha (Sam Ratulangi University, 2023)
Macroalgae are thallus plants that do not have organs in the form of roots, stems, and leaves that are not true. The existence of macroalgae as producer organisms contributes to the life of aquatic biota, especially herbivorous organisms in the waters of Temajo Island, Mempawah Regency, West Kalimantan. This study aims to determine the abundance, relative abundance, relative frequency, diversity index, uniformity index, and dominance index in the waters of Temajo Island. This research was conducted in August 2022, the sampling locations were three stations and were determined using the exploratory method based on the presence of macroalgae found. Macroalgae sampling was carried out using a quadratic transect of 10x10 m and based on the research results obtained 5 families, 3 classes, 4 orders, and 6 genera consisting of Sargassum, Turbinaria, Padina, Halimeda, Codium, and Amphiroa. The results of the analysis found that the genus Sargassum had abundance, relative abundance, and relative frequency (K = 0.72-2.35 ind/m2, KR = 49.99%, F = 0.83) of macroalgae communities in the waters of Temajo Island, Mempawah Regency, Kalimantan West, has a low-medium diversity value, low-high uniformity index and low-high dominance index. Keywords: Community Structure, Macroalga, Temajo Island, Mempawah Abstrak Makroalga merupakan tumbuhan thallus yang tidak memiliki organ-organ berupa akar, batang dan daun tidak sejati. Keberadaan makroalga sebagai organisme produsen memberikan sumbangan bagi kehidupan biota akuatik, terutama organisme-organisme herbivor di perairan Pulau Temajo Kabupaten Mempawah Kalimantan Barat. Tujuan dari penelitian ini yaitu mengetahui kelimpahan, kelimpahan relatif, frekuensi relative, indeks keanekaragaman, indeks keseragaman, dan indeks dominansi di perairan Pulau Temajo. Penelitian ini dilakukan pada bulan Agustus 2022, lokasi pengambilan sampel sebanyak tiga stasiun dan ditentukan menggunakan metode Eksploratif berdasarkan keberadaan makroalga yang ditemukan. Sampling makroalga dilakukan menggunakan transek kuadrat dengan ukuran 10x10 m. Berdasarkan hasil penelitian diperoleh 5 famili, 3 kelas, 4 ordo, dan 6 genera yang terdiri dari Sargassum, Turbinaria, Padina, Halimeda, Codium dan Amphiroa. Hasil Analisa mendapatkan Genus Sargassum memiliki kelimpahan, kelimpahan relatif, dan frekuensi relatif (K = 0,72-2,35 ind/m2, KR = 49,99%, F = 0,83) komunitas makroalga di perairan Pulau Temajo Kabupaten Mempawah Kalimantan Barat, memiliki nilai keanekaragaman rendah-sedang, indeks keseragaman rendah-tinggi dan indeks dominansi rendah-tinggi. Kata kunci: Struktur Komunitas; makroalga; Pulau Temajo; Mempawah